Metabolic Phenotype Characterization of Botrytis cinerea, the Causal Agent of Gray Mold - Wang, Han-Cheng; Li, Li-Cui; Cai, Bin; Cai, Liu-Ti; Chen, Xing-Jiang; Yu, Zhi-He; Zhang, Chuan-Qing (Frontiers in Microbiology, 2018)
Botrytis cinerea, which causes grey mould, is an important pathogen in four important economic crops, tomato, tobacco, cucumber and strawberry, in China and worldwide. Metabolic phenomics data on B. cinerea isolates from these four crops were characterized and compared for 950 phenotypes with a BIOLOG Phenotype MicroArray (PM). The results showed that the metabolic fingerprints of the four B. cinerea isolates were similar to each other with minimal differences. B. cinerea isolates all metabolized more than 17% of the tested carbon sources, 63% of the amino acid nitrogen substrates, 80% of the peptide nitrogen substrates, 93% of the phosphorus substrates, and 97% of the sulfur substrates. The utilization efficiencies of organic acids and carbohydrates were the most informative for carbon sources, and those of amino acids were the most informative for nitrogen sources. Each B. cinerea isolate contained 94 biosynthetic pathways. These isolates showed a large range of adaptabilities and were still able to metabolize substrates in the presence of the osmolytes, including up to 6% potassium chloride, 10% sodium chloride, 5% sodium sulfate, 6% sodium formate, 20% ethylene glycol, and 3% urea. These isolates all showed active metabolism in environments with pH values from 3.5 to 8.5 and exhibited decarboxylase activities. These characterizations provide a theoretical basis for the study of B. cinerea in biochemistry and metabolic phenomics and provide valuable clues to finding potential new ways to manage grey mould.